Solitary sunnah and its legislative value among the Muslim jurists: readings of selected examples - Hashi, Abdurezak Abdulahi (David Publishing, 2013)
The science of hadith authentication and classification (ulum al-hadith) has been developed by Muslim scholars mostly based on critical analysis of the texts and chains of the reports (ahadith) that are attributed to Prophet Muhammad (s.a.w.). Though this science is basically designed to identify the authentic reports which are truly the words, actions or tacit approvals of the Prophet (s.a.w.), however, it has left its implications on fiqh (legal) opinions among the Muslim jurists (fuqaha), who left contrasting legal opinions on certain issues of fiqh, some of which are as a result of their differences on hadith classification, particularly classifications of hadith into solitary and recurrent reports. This paper uses analytical method, and intends to address the implications of hadith authentication and classification methods on the legislative power of the sunnah, with particular emphasis on the solitary sunnah and its legislative value among the Muslim jurists.